Intertextuality in Online News Opinion Article on Industrial Revolution 4.0: Its Type and Discursive Practice - Aan Ramadhansyah Rahayu; Rosaria Mita Amalia (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2019)
This study deals with intertextuality in opinion article on industrial revolution. This study is a part of discourse analysis which aims to discover types of intertextuality in the article and to reveal its social practice (discursive practice).The study follows Fairclough (2003) view of language in use: as an element of social life which is closely interconnected with other elements, therefore this study applied descriptive qualitative method. The results show Implicit Quotation and Indirect Quotation are dominantly used in the articles. Implicit Quotation used as strategy to throw arguments, and Indirect Quotation is used to bring authoritative voice from outside into the articles. The discursive practice of intertextuality in the articles is showing an informal discussion, but still having an academic sense in newspaper article to make it sounds such an authoritative discussion. Therefore, people who read the article would acknowledge the writers’ idea and believe their argument and opinion. Keywords: intertextuality, discursive practice, discourse, online newspaper, opinion article